PENGGUNAAN TINGGI LUTUT DAN PANJANG DEPA SEBAGAI PREDIKTOR TINGGI BADAN DAN INDEKS MASSA TUBUH PADA LANSIA DI KELURAHAN SAMBIROTO KOTA SEMARANG - Riski, Finia; Kartasurya, Martha Irene; Pradigdo, Siti Fatimah (Fakultas Kesehatan Masyarakat, 2018)
The process of degeneration in the elderly less acurate results in height measurement, which has an impact on BMI calculation. Julia Pertiwi created a formula to measure elderly’s height by combining knee height and arm span for Javanese community. The purpose of this study was to determine the compatibility of elderly’s height predictor dan Body Mass Index measurements based on knee height and arm span. This quantitative study used a cross-sectional design. Height was measured by stadiometer, weight by digital scales, knee height by Knee Height Caliper, and arm span by measuring tape. Comparison were conducted through Anova and Kruskal-Wallis tests. This study was conducted on Javanese community in Sambiroto village, Semarang. Fifty two subjects, 18 men and 34 women were aged 60 yeares and over, stand up straightly, and Javanese. Exclusion criteria were hunchback, disability, stiff joints, tremor, fracture, and arm span deformities. The results showed that there was no difference actual height and BMI based on actual height with height and BMI based on Fatmah’s formula (knee height and arm span), Julia’s formula, and Chumlea’s formula on men. There was difference height and BMI based on actual height with height and BMI based on Fatmah’s formula (knee height and arm span), Julia’s formula, and Chumlea’s formula on women. Conclusion: there was a suitability of elderly’s height predictor and BMI measurements based on knee height and arm span. The Fatmah’s formula based on arm span was the best formula for calculating height and BMI on men, and Julia’s formula was the best formula for women, because these formulas had closest results with height and BMI based on actual height. Suggestions for the next researcher should increase the number of samples and be carried out in different ethnicities.